EVALUATING THE EFFICACY OF PERCUTANEOUS DRAINAGE AND SURGERY IN APPENDICULAR ABSCESS MANAGEMENT (The Research of Medical Science Review, 2025)
Background: Appendicular abscess is a common complication of acute appendicitis that can significantly impact patient outcomes. Traditionally, appendectomy has been the standard treatment for this condition, but recent advancements in imaging and minimally invasive techniques have led to the exploration of percutaneous drainage as an alternative approach. This study aims to compare the efficacy of percutaneous drainage versus surgery in the management of appendicular abscess. Objectives: To evaluate and compare the effectiveness, complication rates, length of hospital stay, and post-treatment outcomes of percutaneous drainage versus surgery in patients with appendicular abscess. Study Design & Setting: A prospective, randomized, single-center study was conducted at Shaikh Zayed Hospital Lahore. A total of 130 patients diagnosed with appendicular abscess were included in the study. Methodology: Patients were randomly assigned to either the percutaneous drainage group or the surgery group. The percutaneous drainage group underwent ultrasound or CT-guided drainage of the abscess, while the surgery group received conventional appendectomy. Outcomes were assessed based on abscess resolution, length of hospital stay, complication rates, and the need for repeat interventions. Follow-up was conducted at 30 days post-treatment to assess long-term recovery and recurrence. Results: The study found that 86.2% of patients in the percutaneous drainage group experienced complete abscess resolution, compared to 92.3% in the surgery group. The mean length of hospital stay was shorter for the drainage group (7.2 ± 2.5 days) compared to the surgery group (9.1 ± 3.4 days). The complication rate was lower in the drainage group (15.4%) compared to the surgery group (23.1%). The need for repeat interventions was higher in the drainage group (12.3%) than in the surgery group (6.2%). Conclusion: Both percutaneous drainage and surgery are effective in managing appendicular abscess, with percutaneous drainage offering a less invasive option with a shorter hospital stay and fewer complications. Further research is needed to confirm these findings in larger, multicenter studies.